The research entitled (The Employer's Authorities in Substantially Modifying the Employment Contract) with Wages as a Model - مەحوود, دلاور ساڵح (Sulaimani Journal for Humanities, 2025)
Research Article named (Employer's Powers to Modify the Contract) The Payroll as a Model The contract of employment is classified within the range of contracts obligatory on both sides. Furthermore, this contract is focused on work and the personality of the worker that are taken into consideration. Thus, the principle is the application of the rule of contract (Pacta sunt servanda) in order to strike a balance between the interest of the parties, namely the worker and the employer. Any amendments to the contract of work must resonate the requirements of the work, and its convenience with the social and economic life and technological progress affecting the life in general and the employment contract in particular, and that the amendments must be within the limits of substantive and ostensible controls, on one hand, a wage is all that a worker receives in exchange for a transaction in cash or in kind which he considers to be an essential and intrinsic element of the same contract simultaneously, on the other hand, the source of living of the worker and his dependents, there must be the changes and amendments that shall not affect the worker's living condition. This happens rarely and in very few cases the employer can use and turn to.